Mercados como construções sociais: divisão do trabalho, organização e estrutura social de um mercado em um território municipal - Gustavo Melo Silva (2010)
The market for production of household utensils and decorative pieces from the traditional weaving in Resende Costa City, in the state of Minas Gerais, Brazil has been socially constructed through its inhabitants division of labor, organization and social structure. This production system has its origin in domestic textile production of the eighteenth century in the town then called Arraial da Lage da Comarca do Rio das Mortes in the Capitania of Minas Gerais. Innovations were incorporated to the production process in the twentieth century, compared to the eighteenth and nineteenth centuries, to meet the pressures which permeated the social fabric of those who survived in this regional market place. This market was analyzed as a social construction and characterized by the profile of production, the labor organizations and the social network of traditional weaving. The research has a descriptive-analytical perspective and used case study as method. 2655 households and 76 shops were visited in the urban area. 664 questionnaires were applied at home and 69 at commercial places. They were chosen from a purposive sample of respondents who were directly involved within the market of traditional weaving. The data were organized and analyzed using descriptive statistics, graphical representation of networks; defining the position of these social actors. From the analysis of data, it was found that the market for traditional weaving in Resende Costa went through a series of transformations in the last two decades. These changes were organized bureaucratically and socially; and were controlled by owners of commercial establishments who were holders of supply and consumption sources of home production. This market has been built by a dispersed production in households, by labor division and by trade bureaucratic organization, which controls its productive services to meet, on one hand, the pressures of consumption and, on the other hand, the solidarity between people of a territory in which family relationship constitutes its density and moral discipline.